A comparative evaluation of propranolol pharmacokinetics in obese versus ideal weight individuals: A blueprint towards a personalised medicine. (1st February 2023) - Mortlock, Ryan; Smith, Vivienne; Nesci, Isabella; Bertoldi, Aleesha; Ho, Alexander; El Mekkawi, Ziad; Kakuzada, Lina; Williams, Kylie; Pont, Lisa; De Rubis, Gabriele; Dua, Kamal
Abstract: The pharmacokinetics of propranolol were investigated in obese and healthy weight groups. Research studies in relation to the presented topic were gathered, evaluated, and compared to distinguish variabilities involved amongst different lipophilic drugs and how they impacted the clinical effectiveness. Propranolol is a lipophilic drug so it was predicted that the pharmacokinetics would differ between obese and ideal-weight individuals. Previous research in other lipophilic drugs shows a trend to increase the volume of distribution and half-life in obese compared to ideal weight individuals. However, the majority of both clinical and preclinical studies gathered in this review, found a decrease in the volume of distribution (VD ) and clearance, and minimal significant difference in the half-life, in the obese group when compared with the ideal weight group. Different explanations for this comparison have been theorised including differing tissue blood flow, plasma protein binding, or hepatic clearance in obese compared with ideal weight populations; though the exact reasoning as to why propranolol does not follow the general trend for lipophilic drugs is yet to be determined. These findings regarding propranolol pharmacokinetics can be utilised towards further research and development in personalised medicine for patients with obesity and comorbid cardiovascular disease. The comparative studies highlighted the pharmacokinetic parameters which demonstrated a need for personalised dosage regimes for propranolol and a proposed research direction to understand why the difference exists between these population groups. With the prevalence of obesity continuing to rise, the relative pharmacokinetics of drugs must be evaluated in obese patient groups in order to inform drug dosing regimens and improve current clinical practice. Graphical abstract: Image 1 Highlights: The pharmacokinetics of propranolol vary based on individual body mass index (BMI). The lipophilic nature of propranolol is not the sole reason behind these changes. Consideration of BMI in therapy could improve clinical effectiveness of propranolol.